A new cave-dwelling Maxchernes Feio, 1960 (Pseudoscorpiones: Chernetidae) from Brazil. (2nd January 2023) - Bedoya-Roqueme, Edwin; Tizo-Pedroso, Everton; Barbier, Eder; de Araujo Lira, André Felipe
ABSTRACT: During a survey of caves in a seasonally dry tropical forest area in northeastern Brazil, a new species of the genus Maxchernes was discovered and it is formally described here. The new species, named Maxchernes kapinawai sp. n., has affinities with M. iporangae, known from São Paulo State, Southeast Brazil. The new species, obtained from Pernambuco State, Northeastern Brazil, is characterized by the robust pedipalps, the measurements of pedipalpal femur, and patella different from other known Maxchernes species, in addition to the number of chelal teeth and males larger than females. This new species also represents the north-most record of Maxchernes genera so far. Ecological and conservation comments are included, as well as a map including reports known about the previous species.http://www.zoobank.org/urn:lsid:zoobank.org:act:A0E5D949-5441-4F02-A4BE-9BE51DFEEAFA